Electrospun biodegradable polyorganophosphazene fibrous matrix with poly(dopamine) coating for bone regeneration. Issue 11 (20th December 2013) - Li, Yan; Shi, Yuzhou; Duan, Shun; Shan, Dingying; Wu, Zhanpeng; Cai, Qing; Yang, Xiaoping
Abstract Biodegradable polyphosphazenes were categorized as osteoinductive materials because of their phosphorus‐containing feature; however, they were less supportive in cell attachment and proliferation at earlier points in comparison with biodegradable aliphatic polyesters. Therefore, mussel‐inspired surface modification of poly(alanine ethyl ester ‐co‐ glycine ethyl ester)phosphazene (PAGP) was studied, intending to circumvent the above‐mentioned disadvantage of polyphosphazene. To this end, PAGP and poly(L‐lactide) (PLLA) were electrospun into nanofibrous substrates and surface treated with dopamine aqueous solution. With the analysis of scanning electron microscope, transmission electron microscope, X‐ray photoelectron spectroscope, and Fourier transform infrared spectroscope, the successful poly(dopamine) coating was identified on both PAGP and PLLA nanofibers. MC3T3‐E1 osteoblasts were found attaching and proliferating much well on poly(dopamine)‐modified nanofibrous substrates in comparison with the pristine ones. In addition, the poly(dopamine) coating demonstrated high activity in promoting osteogenous differentiation. Because the phosphorus content on nanofiber surface was decreased with the poly(dopamine) coating, the poly(dopamine)‐coated PAGP nanofibrous substrate was slightly inferior to pure PAGP nanofibrous substrate in osteogenous differentiation. In a summary, the results confirmed that poly(dopamine)‐modified polyphosphazenes were promising scaffold materials with both high cell affinity and high osteocompatibility for bone regeneration. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3894–3902, 2014.